2006
DOI: 10.1111/j.1742-4658.2006.05483.x
|View full text |Cite
|
Sign up to set email alerts
|

Isoquinoline‐1,3,4‐trione and its derivatives attenuate β‐amyloid‐induced apoptosis of neuronal cells

Abstract: Caspase‐3 is a programmed cell death protease involved in neuronal apoptosis during physiological development and under pathological conditions. It is a promising therapeutic target for treatment of neurodegenerative diseases. We reported previously that isoquinoline‐1,3,4‐trione and its derivatives inhibit caspase‐3. In this report, we validate isoquinoline‐1,3,4‐trione and its derivatives as potent, selective, irreversible, slow‐binding and pan‐caspase inhibitors. Furthermore, we show that these inhibitors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Consistently, structural results presented here indicate that only the catalytic cysteine but not the other cysteines in caspase-3 are oxidized to sulfonic acid in the crystal structures of caspase-3 treated with isoquinoline-1,3,4-trione derivatives and DTT. It is likely that the differences among the microenvironment of the active site of the caspases and other cysteine proteases surrounding the catalytic cysteine might render it with varied sensitivities to oxidation, which could explain the phenomena we found previously that these compounds have different selectivity against caspase-3, other caspases, and other proteases (22,23).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Consistently, structural results presented here indicate that only the catalytic cysteine but not the other cysteines in caspase-3 are oxidized to sulfonic acid in the crystal structures of caspase-3 treated with isoquinoline-1,3,4-trione derivatives and DTT. It is likely that the differences among the microenvironment of the active site of the caspases and other cysteine proteases surrounding the catalytic cysteine might render it with varied sensitivities to oxidation, which could explain the phenomena we found previously that these compounds have different selectivity against caspase-3, other caspases, and other proteases (22,23).…”
Section: Discussionmentioning
confidence: 87%
“…The activity of caspase-3, monitored continuously by the production of pNA from Ac-DEVD-pNA, decreased in a pseudo-first order process. Volume dilution and dialysis methods indicated that the inhibition is irreversible (23). The observed rate of inactivation increased nearly linearly with increased concentration of compound III, yielding an apparent inactivation rate constant (k obs /I) of 20,098 Ϯ 867 s Ϫ1 M Ϫ1 within the linear response zone (Fig.…”
Section: Time-dependent Irreversible Inactivation Of Caspase-3 By Isomentioning
confidence: 90%
See 3 more Smart Citations